(3aj eHGOF GdeMGSHI GdeGdjI (B/s - (3fhQ, CMeO eMeOs; (3YKeGf, GdGejQI GHQGgjes ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2000)
(3GSJceGd OhQ GdeMGSHI hGYOGO GdbhGFe GdeGdjI aj GdefTBJ GdJLGQjI hGdUfGYjI(B: (3GSJceGd OhQ GdeMGSHI hGYOGO GdbhGFe aj GdefTBJ GdJLGQjI, GSJceGd OhQ GdeMGSHI hGYOGO GdbhGFe aj GdefTBJ GdUfGYjI aj GdejRGfjI GdYehejI, JUeje GdfXGe GdeMGSHj hWQb GdeMGSHI(B: (3JUeje GdfXGe GdeMGSHj GdeJcGed hGdjhejGJ hGdOaGJQ GdeSGYOI hGdMSGHGJ GdGLeGdjI, GdWQb GdeMGSHjI aj JUMjM CNWGA GdeMGSHI hcjajI eYGdLJgG, GdeTGcd GdeMGSHjI GdeJYdbI HYfGUQ GdCUhd hGdNUhe hGdGaUGM YfgG aj GdbhGFe GdeGdjI(B: (3GdeMGSHI YfO GdCUhd bUjQI GdCLd, GdeMGSHI YfO GdCUhd WhjdI GdCLd, GdeMGSHI YfO GdGdJRGeGJ hMbhb GdedcjIs
Keywords: (3GdeGdjI GdYGeIs; (3GdeMGSHI GdJMdjdjIs; (3GdejRGfjIs